Perbuatan Melawan Hukum Notaris Dalam Pembuatan Akta Perjanjian Pinjam Nama Oleh Warga Negara Asing - Wulandari, I Gusti Agung Ayu Sri; Resen, Made Gde Subha Karma (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022), 2022)
The purpose of writing this research is to examine and analyze the actions of a Notary who makes a deed of a loan agreement in the form of an authentic deed whether it can be categorized as fulfilling the elements as an act of unlawful acts and to examine and analyze the position of the deed if it is used as evidence in court. This writing uses a normative legal research method by reviewing the Denpasar District Court Decision Number 82/PDT.G/2013/PN.DPS and related regulations in entering into loan agreements, applying the statutory and case approach, and using materials secondary law then the results are described descriptively. The results of the study show that the Notary's action in making the Deed of Borrowing Name Agreement as ownership of land rights by Foreign Citizens fulfills the element of an unlawful act that is contrary to the obligations of the perpetrator, and the position of the name borrowing agreement deed which is used as evidence in court does not have perfect evidentiary power and only as evidence under the hand, so that the name borrowing agreement is null and void, but the proof of a deed before the court is submitted to the judge according to the principle of Res Judicata Pro Veritate Habetur which means that the judge's decision must be considered correct